PENGARUH PROFESIONALISME DAN KOMITMEN ORGANISASI TERHADAP KINERJA INTERNAL AUDITOR ( Pada PDAM Kota Bandung ) - Feny Lestari (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2018)
This research purpose to study about the influence of professionalism and organizational commitment toward the performance of internal auditors at PDAM Bandung. The method used in this research is analytical descriptive method. Data collection techniques by literature studies and field studies, used 17 people respondents. Data quality tested by validity test and reliability test. Classic assumption test consisting of multicoleniarity test, heteroscedasticity test and normality test as substantial test for multiple linear regression research. The results of the study show that professionalism and organizational commitment have a positive effect to the internal performance of auditors.